2014
DOI: 10.2147/ott.s61838
|View full text |Cite
|
Sign up to set email alerts
|

High infiltration of tumor-associated macrophages in triple-negative breast cancer is associated with a higher risk of distant metastasis

Abstract: BackgroundTriple-negative breast cancer (TNBC) is associated with poor prognosis and high probability of distant metastases. Tumor microenvironments play a pivotal role in tumor metastasis. Tumor-associated macrophages (TAMs) are one of the main cell components, and they are correlated with increasing metastatic risk. The aim of this study is to analyze the prognostic significance of the infiltration of TAMs in patients with TNBC.Materials and methodsImmunohistochemical staining for cluster of differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 29 publications
(27 reference statements)
5
120
0
6
Order By: Relevance
“…A number of studies have reported that high TAM levels within tumors were linked with local inflammation, angiogenesis, and poor prognosis for cancer patients (27,(42)(43)(44). The present study showed that high levels of scIgGs in breast tumors were also associated with high TAM levels.…”
Section: Elevated Sciggs Parallel Increased Levels Of Mmps In Breastsupporting
confidence: 69%
See 1 more Smart Citation
“…A number of studies have reported that high TAM levels within tumors were linked with local inflammation, angiogenesis, and poor prognosis for cancer patients (27,(42)(43)(44). The present study showed that high levels of scIgGs in breast tumors were also associated with high TAM levels.…”
Section: Elevated Sciggs Parallel Increased Levels Of Mmps In Breastsupporting
confidence: 69%
“…Several studies have indicated that TAMs promote tumor progression and are correlated with poor outcomes in cancer patients (26,27). TAMs are often attributed with the production of multiple cytokines and MMPs in the tumor microenvironment.…”
Section: Increased Sciggs Were Associated With High Macrophage Infiltmentioning
confidence: 99%
“…miR-223 was subsequently reported to promote the invasive potential of breast cancer cells (55 ). In agreement with that observation, a lower rate of overall survival was found in TNBC patients whose tumors had high concentrations of infiltrating TAMs (56 ). Although yet to be investigated, it is possible that exosomal miR-223 from the TAMs may be playing an adverse role here.…”
Section: Natural Killer (Nk) Cells Natural Killer T (Nkt) Cells Cd8supporting
confidence: 66%
“…In tumor microenvironment, macrophages, so called tumor-associated macrophages (TAM), are commonly considered to have M2-macrophage phenotypes characterized as having a regenerative and pro-tumoral function, but not always (Bingle et al 2002, Mantovani et al 2002. Several epidemiological and clinical studies have shown that there are strong relationships between the high density of macrophages and the advanced stage or poor prognosis of various human cancers (Ryder et al 2008, Colvin 2014, Tiainen et al 2015, Yuan et al 2014. However, the opposite results have also shown that a high density of macrophages was associated with better overall survivals in colon (Funada et al 2003, Zhou et al 2010) and thyroid (Cunha et al 2012) cancers, suggesting that macrophages might have wide-raging biological actions in human cancers according to their own tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%